2014
DOI: 10.1371/journal.pone.0106765
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Prediction Model for Screening Bacteremic Patients: A Cross Sectional Study

Abstract: BackgroundBacteraemia is a frequent and severe condition with a high mortality rate. Despite profound knowledge about the pre-test probability of bacteraemia, blood culture analysis often results in low rates of pathogen detection and therefore increasing diagnostic costs. To improve the cost-effectiveness of blood culture sampling, we computed a risk prediction model based on highly standardizable variables, with the ultimate goal to identify via an automated decision support tool patients with very low risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
0
21
1
Order By: Relevance
“…Therefore, we restricted our statistical analyses mostly to single variable methods. Predictive models analysis might increase the discriminatory power of biomarkers [37][38][39]. In a logistic regression model, including LBP, PCT and body temperature, we found 0Á899 ROC-AUC (CI: 0Á813-0Á985) for identifying bacteraemic SIRS patients with neutropaenia.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, we restricted our statistical analyses mostly to single variable methods. Predictive models analysis might increase the discriminatory power of biomarkers [37][38][39]. In a logistic regression model, including LBP, PCT and body temperature, we found 0Á899 ROC-AUC (CI: 0Á813-0Á985) for identifying bacteraemic SIRS patients with neutropaenia.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, in a prospective cohort study including 47 children, no significant difference was found in LBP levels when it came to predicting clinical sepsis or bacteraemia [31]. Predictive models analysis might increase the discriminatory power of biomarkers [37][38][39]. The function of LBP is the binding of bacterial surface patterns including lipopolysaccharides from Gram-negative bacteria and lipoteichoic acid from Gram-positive bacteria [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…Only a few studies have prospectively analyzed the relationship between chills and bacteremia [3,4,[6][7][8][9]28], and none of them have included all patients at the ED where a blood culture had been obtained. Several studies have tried to develop clinical prediction rules to calculate the risk of bacteremia in patients seeking health care with suspected infection [3,4,[11][12][13][14][15][16][18][19][20][21][22][23]. The proposed clinical prediction rules contain between 6 and 20 variables, including clinical parameters, laboratory results, and anamnestic data.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it is important at the population level to identify patients who do not have a bacterial infection to avoid unnecessary use of antibiotics. Other investigators have developed clinical prediction rules for the risk of bacteremia in patients with suspected infection [3,4,[11][12][13][14][15][16][17][18][19][20][21][22][23]. However, these studies have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…86 In this case, BCG-induced training can be interpreted as a particular case of positive NOD-TLR interaction, whereby the first stimulus Fathi et al 91 ), and some studies propose multiparametric prognostic classifiers to identify high-risk patients. 92,93 It is then a matter of clinical trials to determine whether stimulation of innate immunity in these patients would reduce sepsis risk. Given the link between BCG vaccination and reduced sepsis-related mortality in infants, 87 a good starting point could be randomized trials of BCG vaccine administered to highrisk patients on admission to hospital.…”
Section: Prevention Of Infectious Diseasesmentioning
confidence: 99%